PENGARUH MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIKA SISWA - Eka Maria Tinda; Reny Wahyuni; Novianti Mandasari (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2019)
This reseacrh aims to determine the effect of the Missouri Mathematics Project learning model on the ability to think cretaively in mathematics in class VIII junior high school students in the estuary of students in the estuary of 2018/2019 academic year two-variable linearequation system (SPLDV). Jenis type of research used is true experimental design in the form of Pre-test and Post-test design. The population used was all students of class VIII of Muara Beliti state junior high school, consistingof 295 students and as a sample was class VIII.6 with 30 students as dick classes and VIII.8 with 31 students as experimental classes. The data collection was carried out using a test technique in the form of four essay questions with a maximum score of 20. Based on the resultd of the analysis and discussion, it can be concluded that the students creative mathematical thinking ability were obtained then is rejected and is accepted, it means that the average score of students cerative thinking ability using the Missouri Mathematics Project learning model is more than the average score of students creative thinking ability using conventional learning, namely in the experimental class at 12.97 and in the control class at 5.47.